(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
The company SIMTECH RESEARCH SRL completed, in the year 2023, the Project entitled System for the complex diagnosis of the condition of medium and high power rotating electrical machines - acronym SDCME, and in this work the objectives, activities and results of this project are briefly presented, together with the conclusions resulting from the realization of the project, as well as some perspectives on future research.